Hidden powers : Lise Meitner's call to science - Atkins, Jeannine, 1953- (Atheneum Books for Young Readers, 2022)
A biographical novel in verse about Lise Meitner, an Austrian Jew and physics professor in Nazi Germany who escaped to Sweden and whose work led to the discovery of nuclear fission. Includes author's note and timeline.